Gravity Concentration of a Borax Ore from Tincalayu, Salta, Argentine Republic - Mario Zuleta; Carlos G. Rudolp; Julio C. Videla (International Mineral Processing Congress, 2003)
"The present paper summarises the results of gravity pneumatic concentration of a borax ore with 17.5 % B2O3. The sample was extracted from the Tincalayu ore deposit located in the Salta Province of Argentina.The applied methodology was based on a former study (Zuleta, 1985). It consisted of sample characterization by means of physical and mineralogical determinations, chemical analyses as well as pneumatic table concentration tests. In this, a simplified concentrating flowsheet was utilized.A concentrate with 30.6 % B2O3 and 74.7 % recovery was obtained. The recovery was 8.8 % less than previously reported and that was of 30.6 % B2O3 with 87 % recovery. Nevertheless, the simplified flow sheet presented processes only two granulometric fractions, - 6.4 mm + 0.3 mm and - 0.3 mm, compared to the three granulometric fractions used in the previous study: - 6.4 mm + 1.4 mm; - 1.4 mm + 0.3 mm and . 0.3 mm. This would simplify industrial implementation."